Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

y=-2x²-6
y= -(x-3)²+8


Sagot :

Answer:

y=ax2+bx+c is: y=a(x−h)2+k [1]. where h=−b2a and k=ah2+bh+c. Explanation: Given: y=−2x2+6x−3.

Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.